Pouvoirs de pénitencerie et action diplomatique : quelques réflexions autour des dévolutions gracieuses aux légats du pape (fin du XIVe siècle) - Genequand, Philippe (Memini. Travaux et documents, 2021)
Moyen d’action privilégié de la papauté réformée depuis la fin du xie siècle, la légation constitue l’un des outils essentiels de la diplomatie pontificale dans les siècles suivants. Pourtant, si l’on considère les différents pouvoirs attribués aux cardinaux envoyés représenter les intérêts du Saint-Siège, on est frappé de constater qu’ils répondent fort imparfaitement à ce que serait une définition de l’action diplomatique moderne. En particulier, on remarque en leur sein de nombreuses capac...
Keywords: diplomatie pontificale; légation; papauté; pénitencerie

Des florins et des bénéfices : l’appareil fiscal pontifical au temps de la première modernisation des États (xiiie-xve siècle) - Genequand, Philippe (Memini. Travaux et documents, 2018)
Il y a deux façons de comprendre l’adjectif pontifical dans l’expression utilisée en titre. Dans le présent texte, selon l’usage de l’historiographie française, il s’agit de considérer la capacité de ponction du pape sur les temporels ecclésiastiques, et non de faire référence à une fiscalité de nature seigneuriale, fût-elle exercée au profit du pape, et découlant des pouvoirs et des droits exercés sur un territoire et sur les hommes y vivant. Nous utilisons ici les formules « appareil fiscal...
Keywords: Papauté; fiscalité; économie

Quale tipo di modernità alla fine del Medioevo? : problemi e definizioni - Genequand, Philippe (Demodernizzazione : un futuro nel passato, 2021)

Officiers et gouvernement de l'Église sous Clément VII d'Avignon (1378–1394) - Genequand, Philippe (Bibliothèque d'histoire médiévale, 2021)

Le comté de Genève sous administration pontificale (1392-1394): mouvement des hommes, transfert des savoirs - Genequand, Philippe (Bulletin de la Société d'histoire et d'archéologie de Genève, 2011)

Ai piedi del papa: le donne e la Penitenzieria durante il Giubileo del 1500 - Genequand, Philippe (Miscellanea di testi, saggi e inventari dall’Archivio Segreto Vaticano, 2014)

Une politique pontificale en temps de crise: Clément VII d'Avignon et les premières années du grand Schisme d'Occident 1378-1394 - Genequand, Philippe (Bibliotheca Helvetica Romana, 2013)

Templiers et hospitaliers au Moyen-Âge : des frères d'armes - Buffet, Rodrigue (Université de Montréal, 2023)
The Council of Troyes, wich opened on January 13, 1129, confirms an initiative born in the East nine years earlier. Knights had then expressed the will to live in a religious way, by making the triple monastic vow of poverty, chastity and obedience, while continuing to practice the profession of arms in order to protect pilgrims on the roads of the Holy Land. Recognized by the papacy in Troyes and endowed with a rule, the « Poor Knights of Christ and of the Temple of Solomon » became the first military order in history. The Order of the Hospital, which already existed in Jerusalem and whose missions was to care for the poor sick, gradually became militarized in the middle of the 12th century, drawing inspiration from the example of the Temple. Templars and Hospitallers subsequently inspired all other military orders. A historiographical tradition of the Crusades has long maintained the idea of two enemy orders whose conflicts caused the loss of the Latin States of the East. The study of two centuries of common coexistence between Templars and Hospitallers in the Holy Land allows us to bury this image and see how much these military orders influenced each other. It aslo helps to restore the truth about the relationship between the brothers of the two orders. At the frontiers of comparative history, this study follows the chronological framework of the masters of the Temple and the Hospital, making it possible to highlight the importance of the decisions of these men. Thematic studies on the organization of these two orders, their structures, their rules, the images that they transmit and their role in some great events of the Latin States of the East make it possible to understand the links wich united them, as well as the how they influenced each other. We have too often noted their political rivalry, in a kingdom of Jerusalem where the absence of a strong royal power quickly gave them complete freedom. In the same way, we have too often forgotten the price that Templars and Hospitallers paid together on the battlefields of the Holy Land, behaving like what they were : brothers in arms.
Keywords: =CL; Chevaliers; Croisades; Crusades; Holy land; Hospitaliers; Hospitallers; Knights; Medieval history / Histoire médiévale (UMI : 0581); Military orders; Ordres militaires; Religieux; Religious; Templars; Templiers; Terre sainte

Entre la théorie ecclésiastique et la pratique laïque : le mariage chez les fidèles au XVe siècle - Ballard, Alexia (Université de Montréal, 2019)
In the fifteenth century, a valid and legitimate marriage, according to the Church, was monogamous, consensual, exogamous and indissoluble. If it is possible to describe rightly the theory, can we do the same about domestic reality and perception of marriage by the laity? It is to this double question that this master’s thesis seeks to answer. From late antiquity to the late middle Ages, the marriage’s doctrine changed, was refined and finally, fixed. Accordingly, the unions that do not meet these criteria weren’t perceived as legitimate by the ecclesiastical authorities. A non-marital relationship leads to noxious consequences for the couple’s offspring, whose illegitimacy. It’s why the Apostolic Penitentiary graciously intervened by exempting, by absolving and by "leveling" the canon law’s requirements. This office has softened the legislation’s implementation and allowed couples whose marriages were theoretically invalid, to remain married and legitimize their children.
Keywords: Canon Law; Dispensations; Dispenses; Droit canon; History - Medieval / Histoire - Médiévale (UMI : 0581); Holy Roman Empire; Mariage; Marriage; Officiality; Officialités; Penitentiary; Pénitencerie; Saint-Empire romain germanique; The fifteenth century; XVe siècle

La croisade tardive : des plans du début du XIVe siècle à la défaite de Nicopolis - Bontea, Cornel (Université de Montréal, 2014)
L’idée de la croisade reste présente toute au long du XIVe siècle comme bien le prouvent les projets écrits durant le siècle. Les théoriciens de la croisade décrivent minutieusement les mesures à suivre pour récupérer la Terre sainte. Deux éléments sont nécessaires pour pouvoir entreprendre une nouvelle expédition : la paix entre les princes chrétiens et l’union de l’Église. Au XIVe siècle, un transfert s’opère naturellement, et le mouvement de recuperatio de la Terre sainte se projette contre les ennemis les plus proches de la chrétienté, faisant de toute guerre contre le Turc une guerre sainte. À partir de la deuxième moitié du XIVe siècle, la diplomatie joue un rôle crucial dans la prédication de la croisade. Dans ce contexte idéologique, à l’appel du roi de Hongrie, Sigismond de Luxembourg, les puissances chrétiennes tentent de se coaliser pour arrêter l’avancée ottomane en Europe, mais elles sont défaites à Nicopolis, en 1396. Pour la chevalerie française, la campagne était une opportunité de montrer sa vaillance, mais pour elle la croisade prend une allure de chevauchée plutôt que de guerre sainte.
Keywords: Chevauchée; Croisade; Crusade; Crusading; Diplomatie; History - Medieval / Histoire - Médiévale (UMI : 0581); Jerusalem; Jérusalem; Ottoman; Passagium; Preaching; Projects; Projets de croisade; Propaganda; Propagande; Prédication; Saracens; Sarrasins; Turks

La noblesse castillane et la mer durant la Guerre de Cent ans : étude des récits de voyage du Victorial et du Canarien - Bordua, Valérie (Université de Montréal, 2018)
The main purpose of this very text is to study the evolution of the French and Castilian nobilities at the end of the medieval ages through the manuscripts of the Victorial and the Canarian. The development of the nobility’s role is important to see the relationship of some nobles with the oceanic environment and the diplomatic impacts it had created at the beginning of the 15th century. Meanwhile, changes relatively to the relationship between nobility and royalty are also obvious, du to the disruption occasioned by the Hundred Years war. On the other hand, violence at sea also brings an interesting aspect to this study. It helps to understand the upcoming of new responsibilities to the nobles living on the coasts. Finally, the Victorial and the Canarian represent an important side of this work, not only because it shows the stylistic influence of the "amour courtois" literary movement, but also because they are posthumous testimony of the life of don Pero Niño and Jean de Béthencourt. All this proves that, even if the implication of nobles into major enterprises among the sea remains very limited, it is very clear that oceanic side becomes a new reality of war and political alliances at the end of the Middle Ages.
Keywords: Admiralty; Chivalric values; Diplomacy; Diplomatie; Guerre de course; History - Medieval / Histoire - Médiévale (UMI : 0581); Navigation; Nobility; Noblesse; Piracy; Piraterie; Privateering; Royalty; Royauté; Valeurs chevaleresques; Violence at sea; Violence en mer

Enjeux, symboliques et pratiques du don animalier au XIIIe siècle : perspectives conceptuelle, zoologique et historique Faucons, fauves, ours blancs et éléphants - Bouzigues, Benoit (Université de Montréal, 2020)
The main purpose of this text is to study the practices, the issues and the modalities of the animal diplomatic gift in the 13th century, especially during the reign of Frederick II, Henry III and Louis IX. The analysis is based on the presentation of the sociological and anthropological conceptualizations of the gift, particularly those of Marcel Mauss. They are used to understand the peculiarities of the animal diplomatic gift in the 13th century. Then, a research on animal descriptions of medieval bestiaries and encyclopedias is conducted to show the symbolic power and the physical and behavioral characteristics of the offered wildlife. Finally, several modalities of the donation are developed, such as the selection criteria and the wildlife preferences of the kings, the context and rules of the elaboration of a present and the movement of given animals. In addition, it is shown how the beasts and birds had a real use for the kings. Indeed, they staged their animals in order to appropriate their symbolism and show off their prestige and their greatness, at events or in the menageries.
Keywords: Animals; Animaux; Bestiaire; Bestiary; Diplomacy; Diplomatie; Dons; Encyclopedia; Encyclopédie; Exoticism; Exotisme; Gifts; History - Medieval / Histoire - Médiévale (UMI : 0581); Kings; Marcel Mauss; Menagerie; Ménagerie; Prestige; Rois; Symbolism; Symbolisme

Langues, culture et représentation du pouvoir : Jean duc de Bedford, régent du royaume de France (1422-1435) - Cormier, David (Université de Montréal, 2022)
From 1422 the Englishman John of Lancaster (1389-1435), duke of Bedford, was regent of his young nephew’s French kingdom. Because the treaty of Troyes (1420) provided for a long-lasting English presence in France, the regent had to put in place a social domination structure based on consent rather than coercion. In this context, the duke of Bedford devised a cultural and language policy inspired by the attitudes of the most prominent members of the Valois family. It allowed him to bolster support for his regime and legitimize his power. This policy is the main object of our research. We first propose to examine each element of Bedford’s cultural policy. His magnificent households, precious manuscripts and generous patronage were outward symbols of the might and stability of English rule in France. These possessions also allowed their owner to present himself as a legitimate member of continental courtly society. As such, they were a mean to strengthen the bond with his most important ally, his brother-in-law Philip, duke of Burgundy. At the same time the regent depicted himself, and by extension Henry VI, as the legitimate ruler of France by actively imitating past French kings. Some of his cultural enterprises can be conceived as propaganda. However under careful scrutiny these representations of power appear to have been intended not only for the conquered, but also for the conquerors themselves. We devote a second chapter to the exercise of power through writing. We analyze the duke’s production of written documents, both sides of the Channel, in light of its compliance to or defiance of French diplomatic tradition. In itself, the adoption of local practices and language was both respectful of the spirit of the treaty of Troyes and a convenient way to conceal the dynastic rift between Valois and Lancaster. On the other hand, the continued use of typical English documents in Bedford’s organization of the military reveals the limited extent of his acculturation. We also consider the important role of the French secretaries in the coordination between the two kingdoms, which in theory were supposed to be kept separate. Some of them were so involved in English affairs that they moved to England to serve Henry VI. In the end however the English bureaucracy remained mostly unaffected by extraneous innovations. Nonetheless, the very significant linguistic shift it underwent was contemporary, and linked, to the demise of Lancastrian France. The last chapter examines the contribution of other important figures of the anglo-burgundian cultural environment. The continental activity of magnates like Richard Beauchamp and soldiers like John Talbot exemplifies the relative vitality of courtly life in Lancastrian France and highlights the adoption of some elements of French culture by the English there. The subsequent patronage, circulation of texts and artists and, ultimately, the internalization of the Lancastrian French narrative, led to the transformation of English culture. This cultural appropriation contributed to the perpetuation of French language and literature in fifteenth-century England. Paradoxically, it also reinforced a properly English identity.
Keywords: Culture; Fifteenth century; France lancastrienne; French language; Guerre de Cent Ans; Henri VI; Henry VI; History - Medieval / Histoire - Médiévale (UMI : 0581); Hundred Years' War; Jean de Lancastre; John of Lancaster; Lancastrian France; Langue française; Propaganda; Propagande; XVe siècle

L’exercice de la justice en Bresse sous le règne d’Amédée VIII de Savoie (1420-1440) - Darrieu, Jérémie (Université de Montréal, 2018)
In order to standardize the administrative and judicial procedures in a duchy at the heights of its expansion, the duke Amédée VIII of Savoy (1391-1440) adopted in 1430 a set of laws, the « Statutes of Savoy » or Decreta Sabaudiae, which proposed a reform of the State apparatus. But what was the true impact of these Decreta on the exercice of justice in Savoy? This essay seeks to use accounting and fiscal sources from the bailliage of Bresse between 1420 and 1440 in order to determine what were the judicial institutions and practices at the time of the adoption of the Statutes of 1430. A thorough analysis of these new decrees would then establish if they managed to significally change the habits and behavior of the duke’s officiers and subjects. It appears that in the end, the Decreta seeked to correct judicial practices that were neglected over time : the major changes wished by the duke were in fact already established before the adoption of the new Statutes. As for the new penal laws of Amédée VIII, the documentation of Bresse could not prove their concrete enforcement.
Keywords: Accounting; Amédée VIII; Bresse; Comptabilité; Criminality; Criminalité; History - Medieval / Histoire - Médiévale (UMI : 0581); Justice; Officers; Officiers; Statutes of Savoy; Statuts de Savoie

L'étude des dons de dîmes des chambellans de Tancarville à l'abbaye Saint-Georges de Boscherville, 1055-1316 - Desrochers, Simon (Université de Montréal, 2017)
La dîme fut un impôt important qui permit à l’Église de se structurer au Moyen Âge. Elle reste pourtant méconnue des historiens, qui ont surtout considéré ses côtés économiques et religieux. Qu’en est-il toutefois des jeux politiques l’entourant? Poussé par un désir de comprendre la société médiévale et de démontrer les multiples facettes de la dîme, l’auteur de cet ouvrage a analysé trente et une chartes normandes datées du XIe au XIIIe siècle et majoritairement produites par les seigneurs de Tancarville, qui étaient alors chambellans de Normandie. Ces chartes sont presque toutes des confirmations de dons de dîmes destinées à l’abbaye Saint-Georges de Boscherville, nécropole des chambellans qui en furent les fondateurs à l’aube du XIIe siècle, et leur analyse, à la lumière de deux chapitres historiographiques traitant de la dîme, des seigneurs de Tancarville et de l’abbaye, a permis à l’auteur de démontrer que les dons de dîmes ont pu être utilisés dans le but d’affirmer l’autorité des chambellans sur les moines de Saint-Georges ou de faire accepter certaines clauses à ces derniers. L’étude de ces chartes a également permis de découvrir l’existence d’un document falsifié. En même temps, cette étude vient s’ajouter à d’autres plus anciennes pour synthétiser les connaissances et y ajouter une meilleure compréhension des richesses dont a pu jouir l’abbaye bénédictine. Elle vient aussi confirmer la valeur économique importante des dîmes. Enfin, ce mémoire publie quelques chartes inédites et propose une brève analyse du cartulaire de Saint-Georges de Boscherville rédigé au XIIIe siècle et encore méconnu de nos jours. En ce sens, il ouvre la voie à de nouvelles opportunités pour les chercheurs intéressés, puisqu’il effleure le contenu et les détails d’un document massif de deux cent vingt-six folios inédit à ce jour. Ainsi, si cette étude laisse bien des portes ouvertes derrière elle, elle a aussi su en éclairer quelques-unes.
Keywords: Abbaye; Abbey; Cartulaire; Cartulary; Chambellan de Normandie; Chamberlain of Normandy; Confirmations; Donations; Dons; Dîme; History - Medieval / Histoire - Médiévale (UMI : 0581); Normandie; Normandy; Saint-Georges de Boscherville; Tancarville; Tithes; ms. 1227 (Y 52)

Histoire et rhétorique : Grégoire de Tours et les guerres civiles mérovingiennes - Filion, Sébastien (Université de Montréal, 2018)
Grégoire de Tours est l’un des auteurs les plus connus du haut Moyen Âge occidental puisque son œuvre principale, les Histoires, représente notre principale source d’informations concernant l’histoire mérovingienne du sixième siècle. L’objectif principal de cette thèse est de démontrer que ce texte essentiel représente une exhortation destinée à Théodebert II et Thierry II à ne pas s’affronter dans une nouvelle guerre civile. Ce travail est divisé en trois chapitres. L’introduction traite principalement de la question des destinataires visés par Grégoire, c’est-à-dire les fils de Childebert II, et cherche à montrer que les Histoires ont été écrites tardivement dans la vie de l’auteur et non au gré des évènements. Le deuxième chapitre (historiographie, rhétorique et les dix livres d’Histoire) illustre de quelle manière Grégoire a dénoncé la guerre civile et encouragé la collaboration entre les rois grâce aux normes du genre historiographique héritées de l’Antiquité tardive et aux stratégies rhétoriques reprises des écoles tardo-antiques. L’évêque de Tours cherche à souligner les conséquences désastreuses de ces conflits à la fois sur le royaume et la population et à associer ces guerres à des personnages détestés à la cour austrasienne. Le dernier chapitre (le rôle de l’évêque dans les Histoires) démontre que les évêques pouvaient également atténuer ou même empêcher les guerres civiles. Grâce à la représentation de l’évêque idéal transmise depuis l’Antiquité tardive, Grégoire s’est efforcé de valoriser ses collègues qui ont agi pour la paix et de dénoncer ceux qui fuyaient leurs responsabilités ou qui profitaient des tensions pour obtenir des avantages.
Keywords: Bishop; Gaul; Gaule; Gregory of Tours; Grégoire de Tours; Historiographie; Historiography; History - Medieval / Histoire - Médiévale (UMI : 0581); King; Merovingian; Mérovingien; Rhetoric; Rhétorique; Roi; Sixth century; VIe siècle; Évêque

Les intellectuels chrétiens face au Talmud : l’antijudaïsme chez Eudes de Châteauroux lors du procès du Talmud à Paris (1240-1248) - Lecousy, Amélia (Université de Montréal, 2015)
Ce mémoire porte sur l’évolution de l’antijudaïsme chez les intellectuels chrétiens parisiens, particulièrement chez Eudes de Châteauroux, lors du procès du Talmud, c’est-à-dire, entre les années 1240 – année où commence le procès – et 1248, année de la condamnation finale des textes talmudiques. Avec la création des universités au XIIe siècle prend place une curiosité intellectuelle croissante et un désir d’apprendre davantage. Parallèlement à cet essor, l’Église se renforce et une orthodoxie doctrinale commence à s’implanter, avec le désir toujours plus fort de contrôler et d’encadrer les fidèles. Lorsque Nicolas Donin dénonce le Talmud au souverain pontife, en 1239, Grégoire IX demande aux savants chrétiens de l’étudier et de l’analyser. Après examen, ces textes sont condamnés et les juifs accusés de se détourner de l’Ancien Testament pour suivre le Talmud, un livre rempli d’erreurs. Ainsi, ce que nous allons démontrer dans ce travail est que l’antijudaïsme virulent chez Eudes de Châteauroux, lors du procès du Talmud, vient d’une incompréhension des livres talmudiques.
Keywords: Antijudaism; Antijudaïsme; Christian intellectuals; Eudes de Châteauroux; History - Medieval / Histoire - Médiévale (UMI : 0581); Intellectuels chrétiens; Odo of Chateauroux; Paris; Procès du Talmud; Talmud; Talmud trial; Thirteenth century; XIIIe siècle

L'application du traité de Troyes, 21 mai 1420 : au-delà de l'échec, dix années de tentatives et d'efforts au royaume de France - Lemieux, François (Université de Montréal, 2017)
Les termes du traité de paix entre Charles VI et Henri V qui est ratifié par les deux souverains à Troyes en mai 1420 sont plutôt clairs et paraissent aisément applicables : l’unique héritier de Charles VI, le dauphin Charles, est déshérité; Henri V, par le mariage qui l’unit à la fille du roi de France, Catherine, devient le nouveau successeur légitime de Charles VI et, lorsque celui-ci mourra, règnera sur le France et l’Angleterre sans toutefois unir les deux royaumes; le traité scelle aussi l’alliance entre la Bourgogne, l’Angleterre et la moitié nord de la France dans la guerre contre le parti armagnac que dirigie le dauphin Charles et qui contrôle la moitie sud, le royaume de Bourges. Toutefois, lorsque la cérémonie de la cathédrale Saint-Pierre-et-Saint-Paul de Troyes se termine, la théorie du document se heurte à une réalité bien différente. Alors que le traité prévoit une adhésion totale de la moitié nord de la France à la paix et la disparition politique du parti armagnac du dauphin Charles, c’est tout le contraire qui se produit : des mouvements d’opposition ou de résistance au traité et à l’autorité qu’il confère à Henri V comme héritier et régent de France surgissent de toute part et le parti du dauphin, bien loin de disparaître, tient tête à la « coalition » anglo-franco-bourguignonne. À tout cela vient s’ajouter le décès prématuré, en août 1422, d’Henri V qui, lorsque Charles VI le suit dans la tombe en octobre de la même année, laisse les royaumes de France et d’Angleterre entre les mains d’un roi qui n’a pas encore un an. Tous ces faits semblent bien signifier l’échec de la paix et les responsables chargés de l’appliquer en sont tout à fait conscients. Il n’en demeure pas moins que la décennie qui suit la ratification du traité, malgré tout ce qui s’y oppose, est le théâtre d’une véritable tentative d’application de la paix de Troyes ou, du moins, des articles et des éléments de celui-ci que l’ont peut réellement mettre en pratique.
Keywords: Angleterre; Application; Bourgogne; Burgundy; Charles VI; Charles VII; Confiscation; Don; Double monarchie; Dual monarchy; England; English France; France; France anglaise; France française; French France; Grant; Guerre de Cent Ans; Henri V; Henri VI; Henry V; Henry VI; History - Medieval / Histoire - Médiévale (UMI : 0581); Hundred Years'War; Jean de Bedford; John of Bedford; Kingdom of Bourges; Middle Ages; Moyen Âge; Oath; Paix; Peace; Philip the Good; Philippe le Bon; Royaume de Bourges; Serment; Traité de Troyes; Treaty of Troyes; XVe siècle; XVthe century

Dialogue, collaboration et transmission du savoir entre intellectuels juifs et chrétiens : la France des XIIIe-XIVe siècles - Lecousy, Amélia (Université de Montréal, 2020)
This thesis sheds lights on collaborations and transfer of knowledge between Jewish and Christian scholars in France during the 13th and 14th centuries. We propose a comparative analysis of different exchanges, in three distinct areas: theological, philosophical and astronomical. Taking into account the Latin and Hebrew sources that testify this transmission of knowledge, we propose an in-depth study, dividing in two sections. The first part narrates the evolution of education in the Jewish communities and in Christian society. The second part analyses the context of the Extractiones de Talmut, the transmission of knowledge between Maimonides and Thomas Aquinas, the close collaboration between Jacob ben Makhir and Armengaud Blaise, as well as the significant intellectual exchange between Gersonides and his fellow Christians. Our objective is to answer the following questions: did Christian and Jewish scholars receive information according to their own intellectual value, ignoring their source? And was there a direct influence from one scholar towards the other? Thus, this study demonstrates the different motives of these exchanges through a contextual field constituted by a specific intellectual event. We will perceive that these relations vacillate between mistrust and admiration.
Keywords: Christian scholars; Collaborations; Contestations; Fourteenth Century; France; Histoire des intellectuels; Histoire intellectuelle; History - Medieval / Histoire - Médiévale (UMI : 0581); History of scholars; Intellectual history; Jewish scholars; Judeo-Christians relations; Protest; Quatorzième siècle; Relations judéo-chrétiennes; Savants chrétiens; Savants juifs; Thirteenth Century; Treizième siècle

La symbolique des couleurs dans un livre d'Heures du maître de Jean d'Albret (XVe siècle) - Shanks, Francis (Université de Montréal, 2018)
In this master’s thesis, it was mainly a question of the study of colors in a Book of Hours crafted in the late Middle Ages by the master of Jean d'Albret. This type of document was a book of prayer for the laity. Since, this is still a topic that isn’t really studied, it was decided to analyze illuminations found in this Book of Hours. The themes of these are: the Virgin and the Child, the Adoration of the Magi, Bathsheba in her Bath and Saint Michael against Satan. The main objectives of this study were to identify and demonstrate the origins and cultural buildings of the symbolic of colors in these four images. From this research, it came out that the most important and most used colors in the manuscripts are blue, red, gold, green, white and black. First of all, the symbolic of the color blue is love and it comes from the Virgin Mary. Red is the color of the blood of Christ and it most certainly means strength and courage. However, it can symbolize sin as in the case of King David and Satan. For gold, it represents light, therefore, God himself. In the case of the Magi, it is clear that green symbolizes youth through its association with vegetation and spring revival. White represents the purity of Bathsheba and black on the armor of Saint Michael means humility, because of its link with the clothing of monks.
Keywords: Book of Hours; Color; Couleur; Enluminure; History - Medieval / Histoire - Médiévale (UMI : 0581); Illumination; Livre d'Heures; Master of Jean d'Albret; Maître de Jean d'Albret; Middle Ages; Moyen Âge; Symbolic; Symbolique

Les couleurs de la papauté d’Avignon : les manifestations de couleur dans les achats de produits textiles (1316-1378) - Stroykov, Dimitri (Université de Montréal, 2020)
In this master’s thesis, we sought to showcase the permutations of the colours of textile products bought during the sixty-two years under the Avignon papacy (1316-1378). The objective of this research is to develop a systematic and synthetic database that lists the permutations of coloured fabrics purchased by the Avignon papacy in the 14th century that are listed and compiled in the Introitus and Exitus. Our study also aims to explain the trends in the occurrence of these permutations using studies on the symbolism of colours in the 14th century. To be able to analyze the data that we collected and systematized, we called upon additional studies regarding the administration of the papacy, the symbolism of colours in the 14th century, the art of dyeing and the use of clothing. At the end of this study, we can maintain that the Avignon papacy allocates an important role to colours, hence the presence of many colours in the analyzed registers. The manifestations of these various colours are influenced by their symbolism in the 14th century, their dyeing techniques, and the intended use of coloured fabrics. Thus, red, white, green and brown are the most mentioned colours of textile products, these colours being in great demand because of their symbolism and their intended use with the Curia and Panhota. The appearances of gold, orange, violet, silver, purple, gray, black and blue are rarer, because of their price and the difficulties of obtaining fabrics of these colors.
Keywords: Avignon; Colours; Couleur; Dyes; Etoffes; Fabrics; History - Medieval / Histoire - Médiévale (UMI : 0581); Introitus et Exitus; Middle Ages; Moyen Âge; Papacy; Papauté; Symbolique; Symbolism; Teinture; Textiles; Tissu

Rupture et continuité : étude comparative du clergé anglo-saxon du Xe siècle issu de la Regularis Concordia avec le clergé anglo-normand des XIe et XIIe siècles - Simard, Joël (Université de Montréal, 2016)
Ce mémoire a pour but de comparer l’état du clergé anglo-saxon de la période de la Regularis Concordia du Xe siècle, avec celui du clergé anglo-normand d’après conquête situé entre 1060 et 1150. La base de cette recherche se fera à partir des sources narratives les plus pertinentes pour cette période. Mais celles-ci ne seront utilisées qu’en support puisque l’essentiel de ce mémoire sera basé sur le dépouillement des listes d’archevêques, d’évêques et d’abbés ayant vécu entre 1060 à 1150. Nous détaillerons leurs origines géographiques, les charges qu’ils ont occupées durant leur vie de même que leurs réseaux sociaux. Nous tenterons de démontrer que contrairement à l’idée reçue, il n’y eut pas de véritable réforme du clergé anglo-normand suite à la conquête, mais davantage une mise à jour de ce dernier, et qu’en fait, le modèle de gouvernance qui fut imposé au clergé anglo-normand au tournant du XIIe siècle fut largement inspiré du fonctionnement de l’Église normande.
Keywords: Angleterre; Anglo-Norman; Anglo-Normand; Anglo-Saxon; Anselm of Canterbury; Anselme de Canterbury; Christ Church Canterbury; Clergy; Clergé; England; Guillaume Ier; History - Medieval / Histoire - Médiévale (UMI : 0581); Lanfranc; Monachism; Monachisme; Regularis Concordia; William Ist

Baguette, quenouille et clé : le bâton de seidr comme symbole du pouvoir féminin des Scandinaves de l’âge viking - Meilleur, Lou (Université de Montréal, 2024)
Ce travail de recherche porte sur les symboliques de pouvoirs magiques liées à la production du textile en Scandinavie médiévale durant l’âge viking, en particulier sur la quenouille, emblème de la vie quotidienne des femmes vikings. L’analyse établit qu’elle était porteuse d’une pluralité de métaphores magiques et mythiques et était rattachée à une multitude d’objets, de personnages et de créatures de la mythologie scandinave. Cette étude est fondée sur les découvertes archéologiques ainsi que les descriptions textuelles de pratiques cultuelles magiques vikings, et démontre que la quenouille était non seulement perçue comme un outil typiquement féminin au cœur de la production du textile, mais aussi comme un objet fantastique qui permettait de pratiquer la magie. Ces attributs surnaturels jouaient un rôle décisif dans l’expression de l’autonomie et du pouvoir social féminin dans la société scandinave, qui était alors presqu’uniquement centrée sur le masculin. L’indépendance et les privilèges de ces femmes s’articulaient principalement à travers une conception du monde foncièrement issue du polythéisme scandinave, dont le motif le plus important semble avoir été la quenouille. L’hégémonie chrétienne cause la disparition lente de cette base mythologique, et donc des connotations surnaturelles de la quenouille, entraînant avec elles le pouvoir et l’influence sociale des femmes. This research concerns the symbols of magical powers linked to the production of textiles in medieval Scandinavia during the Viking Age as expressed through the distaff, emblem of the daily life of Viking women. The analysis establishes that distaffs represented a variety of magical and mythical metaphors, and were also associated to multiple objects, characters and creatures in Scandinavian mythology. This study is based on archaeological discoveries and textual descriptions of viking magical cult practices and demonstrates how the distaff was perceived not only as the heart of ancient textile production, but also as a fantastical and characteristically feminine object that could achieve a variety of magical acts. These supernatural attributes played a decisive role in the determination and the expression of female autonomy and power in the male-centric Viking society. The independence and privileges of these women hinged on the Nordic mythological world, and its main motif seems to have been the distaff. With the spread of Christianity in the Scandinavian world, this polytheistic understanding of the world slowly disappeared, alongside the magical connotation of the distaff, and with it, the social power and influence of women.
Keywords: =CL

Partager le savoir et non propager la peste : étude du Livre des mortalités - Paquette, Emmanuelle (Université de Montréal, 2024)
En 1425, dans un royaume de France déchiré par la guerre civile, contrôlé par les Anglais et rongé par les épidémies de peste, un certain Olivier de la Haye publia le Le livre des mortalités. Cette oeuvre était une traduction française du Compendium de epidemia, un traité de peste écrit par la Faculté de médecine de l'Université de Paris à la demande du roi Philippe VI de Valois suite à l'apparition, en 1348, de l'épidémie de peste noire sur le territoire français. Bien qu'il existât alors deux autres traductions françaises de ce teste, l'oeuvre d'Olivier de la Haye se démarqua immédiatement de celles-ci en raison de sa forme. En effet, le Livre des mortalités n'est pas seulement une adaptation française de la compilation parisienne, c'en est aussi une versification, qui comporte plusieurs éléments originaux ajoutés au texte latin. Ce mémoire s'intéresse aux modifications présentent dans le Livre des mortalités ainsi qu'aux motivations derrière les choix de l'auteur. En positionnant le poème d'Olivier de la Haye au coeur de cette étude et en adoptant une approche se situant au croisement de l'histoire médicale, littéraire et linguistique, ce mémoire se distingue de la recherche existante qui délaisse cette source au profit des deux autres traductions françaises du Compendium. Grâce à la présentation du contexte de production du Livre des mortalités, cette étude relève l'influence de la situation sociopolitique sur l'écriture et sur les éléments originaux du poème. L'analyse de ses particularités, qu'elles soient liées à la matière médicale du Livre des mortalités ou à sa forme littéraire, indique la volonté d'Olivier de la Haye de produire une oeuvre didactique lui permettant de partager son savoir à un public de praticiens.
Keywords: =CL

Énigmes mathématiques au temps de Charlemagne : à propos des propositiones pour aiguiser l'esprit des jeunes - Gavin, Jérôme; Genequand, Philippe (Histoire des mathématiques, 2021)

Prédication et politique à la cour d'Avignon : Pierre Roger (Clément VI) et la croisade - Genequand, Philippe (Preaching and political society : from Late Antiquity to the end of the Middle Ages = depuis l'Antiquité tardive jusqu'à la fin du Moyen Âge, 2013)

Réception et usages des principes du droit romain par les officiers royaux français : réflexions autour de la justice pénale sous Charles VI (1380-1422) - Perreault-Corbeil, Élisabeth (Université de Montréal, 2023)
The reign of Charles VI (1380-1422) of France is characterized by several upheavals, the first one being the king's madness, declared in 1392. Despite the military, economic and social crises that shake the kingdom, it is nevertheless a strong time for the establishment of the monarchical State. The instability actually allowed the royal authority to strengthen its positions and to impose its power more effectively, especially in matters of justice. This strengthening is grounded on the Roman law, which had been studied since the 12th century by royal officers, important members of the administration. The present work analyzes the way legal principles inherited from Antiquity are received and engaged in medieval literature to support thoughts on justice. It is based on the study of the writings of four influential royal officers: Nicolas de Clamanges, Jean de Montreuil, Laurent de Premierfait and Guillaume de Tignonville. The concepts borrowed from the classical works are expressed through a double affirmation: a more severe application of royal justice and a more systematic use of the death penalty. If the authors expectations are sometimes incompatible with an exercise of justice guided by clemency, the royal authorities nevertheless tend to sanction more rigorously. The relationship between legal theories and their application is complex, but tends to converge towards the same path, in the context of the affirmation of sovereignty and the fight against crimes that threaten public peace.
Keywords: 14th-15th centuries; =CL; Death penalty; Droit romain; France; Guillaume de Tignonville; Jean de Montreuil; Justice; Laurent de Premierfait; Medieval history / Histoire médiévale (UMI : 0581); Nicolas de Clamanges; Peine capitale; Roman law; Souveraineté; Sovereignty; XIVe-XVe siècles

La gestion des forêts royales en Normandie à la fin du Moyen Âge : étude du Coutumier d’Hector de Chartres - Lake-Giguère, Danny (Université de Montréal, 2015)
Au début du XVe siècle, les forêts domaniales devinrent un enjeu majeur dans les affaires du royaume de France. Gérées par l’administration des Eaux et Forêts, elles furent sur ordre du roi l’objet d’une surveillance particulière. L’étude du Coutumier d’Hector de Chartres, un registre du XVe siècle consignant les droits d’usage de centaines d’usagers des forêts du domaine normand de Charles VI, révèle la place que ces dernières occupaient dans la société en France dans les derniers siècles du Moyen Âge. D’une part, le Coutumier démontre qu’elles étaient non seulement importantes dans l’économie de la province mais qu’elles jouaient aussi un rôle essentiel dans la vie autant à la campagne que dans les villes. D’autre part, avec l’analyse des ordonnances forestières du XIVe siècle et du début du XVe siècle, il illustre comment elles furent d’une importance capitale pour le roi puisque ce dernier y prenait le bois nécessaire à la construction de sa marine et à l’entretien de ses forteresses normandes et qu’il en tirait d’importants revenus dans un contexte d’hostilités avec l’Angleterre. Ainsi, une relation de réciprocité bénéfique pour le roi et les usagers s’installa à travers un complexe système d’usages et de redevances. En cherchant à protéger ces bénéfices, les rois de France tentèrent de gérer adéquatement leurs forêts, établissant ainsi les jalons d’une foresterie durable tournée vers la préservation des ressources sylvicoles et se posant en gardiens du bien commun.
Keywords: Coutumier; Customs; Droits d'usage; Eaux et forêts; Forest; Forêt; Gestion durable; Hector de Chartres; History - Medieval / Histoire - Médiévale (UMI : 0581); Normandie; Normandy; Reformation; Réformation; Sustainable management; Waters and forests administration

Le banquet comme vecteur de la christianisation en Norvège médiévale - Ouellet-Ayotte, Jérôme (Université de Montréal, 2018)
This study concerns the christianization of medieval Norway, from the eleventh century until the mid-thirteenth century, through feasts and food rituals. The analysis is largely based on the Gulathing law, a legal compilation of regional laws started in the eleventh century and codified in its final form in the thirteenth century. A few other sources act as auxiliaries, especially helpful in the establishing the chronology of christianization. Throughout this work, the marked importance of feasts as an essential mechanism to the Norwegian society allows to better understand how these events served the religious transition. This work also establishes that christianization was a lengthy process where a few elements of religious continuity could be observed. The feasts proved to be an important means to the coming of Christianity in the North, mostly through the retaining of certain rites and through the cultural changes observed in this kind of event.
Keywords: Gulathing Laws; History - Medieval / Histoire - Médiévale (UMI : 0581); Middle Ages; Moyen Âge; Norvège; Norway; banquets; christianisation; christianization; feasts; lois de la Gulathing; paganism; paganisme; rites

Représentation et altérité : la vision du païen par les chrétiens latins de Charlemagne aux croisades de Prusse - Provost-Brien, Louis (Université de Montréal, 2019)
Paganism was a European reality for most of the medieval period. Missionaries and monarchs worked to reduce it through proselytism, conquest and assimilation of the various pagan populations. Many texts bear witness to these contacts between Christians and idolaters, while the chroniclers, recounting great events of their time, had no choice but to speak of the conflicts that broke out between them. Possessing writing unlike their pagans’ counterparts, Latin Christians thus left their vision of these strange adversaries. Tinged with numerous filters, the latter in no way represented historical reality, but rather the perception maintained by the elite with regard to heathenism. Thus, in this study, we propose to study this vision of otherness, while we examine the accounts of these contacts between Christianity and their pagan neighbours. Focusing on the period between 772 and 1283, we propose a case study, composed of four sets. In the first chapter, Charlemagne’s war against the Saxons between 772 and 804 will be discussed. Then, we will approach the Slavs who were fought by the Ottonians and the Salians between the Xth century and the great revolt of 1066. Third, we will focus on the Wendes against whom crusades were carried out between 1147 and 1185. Finally, we will conclude this analysis with a study of the Prussians during the crusades against them in the 13th century. By a qualitative analysis of the vocabulary used to characterize the heathens, we can highlight certain characteristics attributed to them, allowing, in conclusion, a comparative analysis thereby allowing a portrait of the evolution of the representation of pagans.
Keywords: Heathen; Heathenism; History - Medieval / Histoire - Médiévale (UMI : 0581); Idolâtre; Idolâtrie; Pagan; Paganism; Paganisme; Païens; Prussians; Prussiens; Religion; Representation; Représentation; Saxons; Slaves; Slavs; Wendes

Âge, éducation et compagnies de jeunesse à Venise, début du XVIe siècle - Trottier-Gascon, Caroline (Université de Montréal, 2017)
This dissertation inserts the compagnie della calza within the life paths of Venetian patricians. After a theorisation of age as a system of categories, we describe how the institutions regulating age in the Venetian Republic worked before the mandatory registration of birth (starting in 1506). We then show how participation to compagnie della calza was part of the education process of young patricians, in parallel to their progressive assimilation into republican institutions. Therefore, we argue that the transformations of age regulations in the first third of the 16th-century contributed to the disappearance of the compagnie della calza : after 1531, the opening of the office of savio ai ordini to 25 year olds instead favoured the education of elite patrician youth within republican institutions, which impacted the purpose of the companies. Finally, we offer a case study of two companies, the Reali and the Floridi. By following the political careers of former members, we confirm the hypothesis put forward by Robert Finlay of a Venetian gerontocracy dominated by the oldest of patricians.
Keywords: Age; Age qualifications; Career; Carrière; Compagnie della calza; Gerontocracy; Gérontocratie; Histoire; Histoire vénitienne; History; History - Medieval / Histoire - Médiévale (UMI : 0581); Jeunesse; Limites d'âge; Patricians; Prosopographie; Prosopography; Venetian history; Venice; Venise; Youth; Âge

What Kind of Modernity at the End of the Middle Ages? Problems and Definitions - Genequand, Philippe (Demodernization: a future in the past, 2018)

Les discours de Pierre Plaoul au Parlement de Paris (1406) : un exemple des rhétoriques française et latine au Moyen Âge tardif - Cormier, David C. (Université de Montréal, 2015)
Le 27 mai 1406, le théologien parisien Pierre Plaoul comparaît devant la cour du Parlement de Paris en tant que représentant de l’Université de Paris dans une affaire qui l’oppose à l’Université de Toulouse. Il y prononce un sermon en latin, ce que la cour lui reproche instantanément, lui demandant de parler en français pour la prochaine séance. Le 7 juin, lors de sa deuxième comparution, il parle cette fois en langue vernaculaire et prononce un discours extrêmement différent du premier, autant dans son genre que dans son registre de citations. Les deux discours sont conservés dans le registre X1a4787 des Archives nationales de France. L’édition des discours permet de comprendre le raisonnement derrière leurs différences, mais il permet surtout de constater que le discours français fait état d’une érudition encore plus grande que son homologue latin et que son orateur n’était nullement gêné par l’usage de la langue vernaculaire. Remis dans le contexte historiographique actuel, il en ressort que l’utilisation du français par Plaoul concorde parfaitement avec l’abandon du modèle de rapport diglossique entre latin et français pour la fin du Moyen Âge, lui préférant plutôt un rapport de langues en contacts. Ce postulat est soutenu par les nombreuses occurrences d’universitaires médiévaux démontrant une excellente maîtrise d’un registre savant de la langue vulgaire, des poètes, aux prédicateurs en passant par les practiciens du droit. Un examen plus attentif de l’utilisation de la langue française par les docteurs en théologie du règne de Charles VI vient aussi appuyer l’hypothèse selon laquelle les universitaires du bas Moyen Âge considéraient la langue vernaculaire comme un instrument approprié à la transmission de la culture savante.
Keywords: Epistola tholosana; Faculty of theology; Faculté de théologie; Français; French; Grand schisme d'Occident; Great schism; History - Medieval / Histoire - Médiévale (UMI : 0581); Latin; Middle Ages; Moyen Âge; Pierre Plaoul; University of Paris; Université de Paris

Le dauphin et l’astrologue : le Livret des elections universelles des 12 maisons de Pèlerin de Prusse - Gaignard, Floriane (Université de Montréal, 2015)
In 1361, at Hotel St-Pol, the future king of France, Charles the Fifth, received a book entitled Livret des elections universelles des 12 maisons from his astrologer, Pèlerin de Prusse. Written in old French during the translatio studii period, the book contains two books and describes several astrological theories along with precise descriptions of the twelve houses. Charles the Fifth is widely known as Charles the Wise in our present day. This is due to his vast contributions to the Louvre library as well as his impulse of translations from Latin to the French of the auctoritates and his passion for astrology. The significance imparted on astrology prior and during Charles the Fifth’s reign is apparent in Pèlerin de Prusse’s text Traité des elections, commissioned by Charles during a time of political unrest. The defeat of Poitiers, the États of 1356 to 1358 as well as the Jacquerie define the political landscape of 14th century France. Located at Oxford and the Vatican, two copies are extant, and neither have been edited from the original or subjected to detailed examination and study. This master will present a transcription of the first part of the Livret des elections universelles des 12 maisons.
Keywords: Astrologie; Astrology; Astronomie; Astronomy; Charles V; Fourteenth Century; France; History - Medieval / Histoire - Médiévale (UMI : 0581); Livret des elections universelles des 12 maisons; Pèlerin de Prusse; XIVe siècle

Administrer les forêts du roi au Moyen Âge : le negocium forestarum en Normandie capétienne (1204-1328) - Lake-Giguère, Danny (Université de Montréal, 2021)
In 1346, Philip VI of Valois enacted the Ordinance of Brunoy. This lengthy document aimed at reorganizing the kingdom’s forest administration in order to ensure that royal forests remained sufficiently profitables and adequately managed. For most of the past century, historians have believed the Ordinance of Brunoy to be the first true expression of the forest policies of the French crown. In reality, Philip VI benefited from a wealth of regulations already in place which had been developped by his predecessors since the beginning of the XIIIth century. It can be argued that the reign of Philip Augustus, and especially his conquest of Normandy in 1204, truly marks the inception of the first forest policies by the French royal government. From that time on, royal forests in Normandy were managed according to a set of strict regulations aiming at limiting usage rights and guaranteeing a steady contribution to the kingdom’s finances. Forests during the Middle Ages served multiple purposes : beside their input in royal finances, they were vital to rural economy, and formed a space over which medieval princes exercised their justice, authority, power and generosity. The study of administrative sources from XIIIth and XIVth Normandy gives a better understanding of the development of these early policies, which revolved around the creation of a new administration headed by the masters of « Eaux et Forêts » and the formulation, under the auspices of common good, of a set of rules and regulations aiming at maintaining a balance between conservation, exploitation and usages. In truth, the forests of medieval Normandy were far from the archetypal woodlands of medieval litterature : they appear as a well delimited and rationalized space, managed and monitered by the king’s officers, and formed an area of contact and conflict between the royal government and the forests’ users.
Keywords: Eaux et Forêts; Economy; Environment; Environnement; Forest; Forest Administration; Forêt; France; Histoire; History; History - Medieval / Histoire - Médiévale (UMI : 0581); Middle Ages; Moyen Âge; Normandie; Normandy; Économie

Le banquet en Norvège et en Islande aux XIIe et XIIIe siècles - Ouellet-Ayotte, Jérôme (Université de Montréal, 2023)
This thesis explores feasting in Norway and Iceland during the 12th and 13th centuries. The subject of this work, often only merely mentioned by historiography, aims to fill this need by painting a general picture of banquets during the chosen time period. We aim to specifically address the topic by garnering exceptional details present in historical documents. This study also wishes to establish the various roles played by banquets by following two main axes. The first one sees the feast serving as a conveyer of social cohesion and friendships and also as a building tool for relationships. Inversely, the second exposes how feasts could serve more hostile purposes, notably distinguishing every attendee and underlining social inequalities among a given group. We also aim to categorize feasts, to identify their uses and their breadth. Through these efforts, we also identify unique traits that define this practice around western Scandinavia, but also the differences it entertains against other European regions. Finally, this study aims to touch on the transmission of customs surrounding feasting from Norway to Iceland incidental to increasing political relationships. To achieve the aforementioned goals, we solicited the use legal texts from both regions, king sagas, contemporary sagas, as well as documents coming from the Norwegian court.
Keywords: 12th century; 13th century; =CL; Banquet; Coutumes et moeurs; Customs; Distinction; Feast; Iceland; Islande; Laws; Lois; Medieval history / Histoire médiévale (UMI : 0581); Norvège; Norway; Sagas; Sociability; Sociabilité; XIIIe siècle; XIIe siècle

Le débat sur la Bible en langue vulgaire, 1540-1562. Deux traités de Pierre Viret publiés anonymement - Paquin, René (Université de Montréal, 2021)
A direct access to the foundational texts of the Christian faith in vernacular languages was part of the basic demands of the Protestant Reformation in the 16th century. The French linguistic domaine was no exception in this regard. Henri Estienne, in his Apologie pour Hérodote, alludes to a specific anonymous literature dedicated to this question in response to biblical censorship in the 1540’s. Our investigations in these primary sources lead our attention on two pamphlets which have remained almost unknown to most bibliographers: 1) TRAICTE AUQUEL / est deduict s’il est loisible de / lire la saincte Escriture en / langue Vulgaire, & / du fruict qui en peult sortir. (s.l.n.d. , 80, italique, 94 p., signé a-f8, marginales, titres courants, 2 initiales ornées (a 2r0; 3v0). 2) TRAITE, / QU’IL EST NECESSAIRE / QUE TOUTES GENS DE QUEL- / que qualité, sexe, ou aage, qu’ils / soient, lisent les Saintes Escri- / tures : Et du moyen qu’on / y peut tenir. (s.l., s.n., 1561, avec une marque aux palmes du martyr couronnées), 80, italique, 36 ff., signé A-D8, E4, marginales, titres courants, 1 initiale (Aii ro). These two treatises clearly disclose a protestant and reformed content. Moreover, the numerous biblical, literary and patristic quotations they contain, more specificaly the 1561 edition, show that they where penned by master’s and not by disciples. Many candidates to their authorship have been considered and among these it is the religious work of Pierre Viret that offers the most ressemblances with the two pamphlets. The observations summed up to this day have convinced us that the first booklet, published in 1544 and mentioned for the first time in 1549 in the Parisian catalogue of prohibited books (Index de Paris, with the notice 1543) forms the editio princeps of an unprecedented work of the Swiss Reformer. It is part of our thesis that this booklet was later completely rewritten by Pierre Viret and published in Paris in 1561 under a new title. The Viretian paternity of these two tracts will be proven in the present research with the help of quotations, textual connections and other arguments based on the internal and external criticism of primary sources. Here follows a brief summary of our demonstration. The analysis of the first booklet (henceforth: T1) reveals a tight relationship with the style and ideas of Pierre Viret as can be seen in his works printed between 1542 and 1555. Among the reminiscent passages, one must point out many borrowings from De la difference qui est entre les superstitions et idolatries des anciens gentilz et payens… (Geneva, 1542), an important work which Viret has often reused in his subsequent writings. We also found a brief extract of T1 in the Dialogues du desordre qui est a present au monde (Geneva, 1545) and in the Métamorphose chrestienne (1561), which prove a later reuse of this source by Viret. A carefull reading of T1 also reveals an import from Marie Dentière’s Epistre tresutile (1539) and Calvin’s Epistre monstrant comment Christ est la fin de la loi (1543). Our findings have also allowed us to put forward plausible and instructive suggestions, which still need to be validated, regarding the immediate editorial context of T1. On this matter, one will note that T1 was released when editions of the Bible, the Psalter and the New Testament were regularly and largely printed both in Geneva and Lyon. These geographical area were two biblical publishing centers following very similar patterns of eristic and religious discourses. Several issues were parts of confessional polarization on both sides. Our research on T1 was extended with the discovery of the 1561 treatise mentioned earlier (henceforth: T2). A carefull comparison of the two treatises suggests that latter is a profoundly reviewed reedition of the former. We are the first to have made this connexion. Viret’s well known literary habits, specially since the mid 1550’s, confirm this hypothesis. However a meticulous comparative study between T2 and Viret’s contemporary writings had to be undertaken before drawing any conclusion. The results of the inquiry are eloquent: T2 overlaps with most of his books published between 1559 and 1565 (strict textual kinship of ideas and style, verbatim recoveries, paraphrases). T2 even picks up a short extract from an important work De la difference qui est entre les supersitions (1542), a book we have underscored, with other historians, the value in Viret's bibliographical and literary repertoire. In short, our findings can be summarized as follows: T1 borrows from Viret, Viret borrows from T1 and T2, and the latter draws from T1 and Viret. Viret probably composed T2 shortly after he left Geneva for France (at the end of September 1561). Nîmes is the most likely location where he wrote this tract. Internal indications, to which external testimonies can be added, lead us to think that Viret wrote this short pamphlet with the intention of rallying the King of Navarre, his court and the nobility to the Reformed faith that is at a key moment when the Huguenots where largely increasing in numbers accross the kingdom, especially in the Southern cities where highly ranked families and many intellectuals enthousiastically clinged to the protestant theses. Hence, in the beginning of the 1560’s, Hugenots where forming a genuine political strength capable to inflect the Kingdom’s destiny in its most sensitive center: the monarchy. T2's context falls in line with the colloque de Poissy, an important event that took place in Paris between September 9 and October 14, 1561. There are reasons to believe that Viret's second treatise was largely disseminated in the French capital city since the printed typographical characters match those used by Nicolas Edoard and Charles Pesnot, namely two protestant printers active at the time of the Poissy colloquium. Differing on this particular point from T1, T2 was thus produced at a time when the process of "confession-building" of religious discourses was making it all the more evident that two conflictual and irreconcilable ecclesiologies were at stake within the same kingdom. In short, the religious debates where now deploying under a political spin. Hence, T2 appeared at a very critical moment when religious debates revolved around the political implications of the decline of the Catholic Valois and the rise of the Protestant Bourbons. Less than a year after the publishing of T2, on 2 April 1562, Condé and his Protestant followers seized the city of Orléans. Their example was soon followed by Protestant groups across the realm. The same year saw the outbreak of the first of the eight religious wars that would plague the kingdom during the rest of the century. By his immense literary input, to which our thesis now adds two new primary sources (which the reader will find herein with scientific annotations), and by his intensive fieldwork as a reformer – both in the Genevan-Swiss milieu and in France since the early 1560’s up until his death in 1571 (one year before the St. Bartholomew's Day massacre) – Pierre Viret will have not only been an important witness but a leading protagonist of the debate over the democratization of the Bible in the vernacular and the theological evolution surrounding this major controversy of the Reformation and post-Reformation era.
Keywords: Bible; Calvinism; Calvinisme; Censorship; Censure; Culture populaire; Democratization; Démocratisation; History - Modern / Histoire - Moderne (UMI : 0582); Inquisition; Knowledge; Popular culture; Renaissance; Savoir; Traduction; Translation

Kardinäle, Schisma und Konzil: das Kardinalkolleg im Grossen Abendländischen Schisma - Genequand, Philippe (Geschichte des Kardinalats im Mittelalter, 2011)
Keywords: _CL

Le souverain, l'office et le codex: gouvernement de la cour et techniques documentaires à travers les Libri officiariorum des papes d'Avignon (XIVe-XV siècle) - Genequand, Philippe; Anheim, Étienne; Butaud, Germain (Sources et documents, 2014)

Des ombres aux chapeaux rouges. Pour une nouvelle histoire des cardinaux à la fin du Moyen Âge - Genequand, Philippe (Église et État, Église ou État? : les clercs et la genèse de l'État moderne : actes de la conférence organisée à Bourges en 2011 par SAS et l'université d'Orléans en l'honneur d'Hélène Millet, 2014)

Sommes-nous des porcs ou des chevaux? Familiarité et distinction entre humains et animaux dans les derniers siècles du Moyen Âge - Genequand, Philippe (Les animaux... l'histoire continue: rencontres pluridisciplinaires autour de Robert Delort, 2022)

Journal de Jean Le Fèvre: Chancelier des ducs d'Anjou et comtes de Provence, 1381-1388 - Hébert, Michel; Matz, Jean-Michel (Mémoire commune, 2020)